Dietary pattern and risk of thyroid cancer: a systematic review and meta-analysis protocol - Kleyton Santos Medeiros; Jose Brandao-Neto; Yasmin Guerreiro Nagashima; Aline Alves Soares; Camila Xavier Alves; Marcia Marilia Gomes Dantas Lopes (BMJ Open)
Introduction Until now, the thyroid cancer case number has increased, and it is not entirely possible to attribute this continuous growth to more meticulous thyroid nodule selection and more accurate diagnostic techniques. While there is currently no conclusive evidence linking dietary factors to thyroid cancer, certain dietary patterns seem to have an impact on the development of the disease. There are interesting connections among diet, environment, metabolism and thyroid carcinogenesis; a deeper comprehension of the underlying mechanisms should help the identification of modifiable risk factors for thyroid cancer. This protocol aims to guide a systematic review and meta-analysis of the literature to search for an association between dietary pattern and risk of thyroid cancer.Methods and analysis The databases to search for observational studies will be PubMed, Embase, Scopus, Web of Science and LILACS, from inception to 10 December 2024. No language limitation or publication period will be imposed. The outcome will be the patients with thyroid cancer. Three impartial reviewers will choose the studies and extract data from the original publications. The Newcastle-Ottawa Quality Scale will assess the risk of bias, and the certainty of the evidence will be achieved by using the Grading of Recommendations Assessment, Development and Evaluation. The R (V.4.3.1) will be performed for data synthesis, and to measure heterogeneity, we will compute the I2 statistics. Additionally, a quantitative synthesis will be performed if the included studies are sufficiently homogenous.Ethics and dissemination It is not necessary to acquire ethical approval, as this study will be a review of the published data. A peer-reviewed publication will publish the systematic review’s findings.PROSPERO registration number International Prospective Register of Systematic Reviews (PROSPERO) CRD 42023463802.